Lexical Innovation in Digital Space as an Effort to Preserve the Riau Kampar Malay Language - Juli Yani; Raja Syamsidar; Rerin Maulinda; Roziah Roziah; Hadi Wibowo (Journal of General Education and Humanities, 2026)
The threat to regional languages posed by globalization has spurred lexical innovation in digital spaces to preserve language. This phenomenon is influenced by various factors, including dialect variation, geographical boundaries, number of speakers, place of residence, identity and cultural pride, as well as socio-economic conditions. This study aims to identify (1) complete lexical forms, (2) semantic fields that exhibit complete lexical forms, and (3) complete lexical forms that undergo variation in the Riau Malay language in Kampar Regency. This research employs a descriptive qualitative method, with data collection techniques including observation, interviews, and audio recording. The results show that complete lexical innovation comprises 29 glosses with 98 variants across eight observation points in Kampar District. The semantic field with the highest occurrence of complete lexical forms is the domain of house and its surroundings, consisting of 7 complete lexical items with 23 variants. Additionally, the lexical forms with the greatest variation reach four variants across two glosses, namely kakaɁ laki-laki in Riau Malay in Kampar. Lexical innovation, particularly in digital spaces, plays an important role in maintaining and preserving regional languages, especially Riau Malay in Kampar Regency.